The Determination to achieve one’s Goals Facing Adversity in Second Class Citizen (1974) and Head above Water (1986) - Sene, Abdou (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Many an African woman writer entered the literary field or has been made famous in this field through the publication of an autobiography. Thus, the 1970s and 1980s, which correspond to the early years of African women’s writing, were marked by the production of a multitude of autobiographical novels by African female writers. Beyond the articulation of their life experiences, these writers not only raise African women’s awareness about their condition in society but they also denounce the victimization of women due to the patriarchal system. Among these authors, one can cite Buchi Emecheta who explores in Second-Class Citizen (1974) and Head Above Water (1986) issues such as culture, gender, psychology, sociology, racism, etc. Leaning on feminism, culture, gender, psychology, sociology and racism as theories, this paper is going to deal with the determination to achieve one’s objectives facing adversity in these two novels. To this end, the article will analyze the obstacles which Emecheta faced before going to the country of her dreams (the UK). Then, this study will zero in on the sacrifices she made in order to be a writer. Finally, this work will focus on the problems related to flat renting which Buchi had been confronted with and which pushed her to difficultly buy a house in London.